Druggable Hot Spots in the Schistosomiasis Cathepsin B1 Target Identified by Functional and Binding Mode Analysis of Potent Vinyl Sulfone Inhibitors - Jílková, Adéla; Rubešová, Petra; Fanfrlík, Jindřich; Fajtová, Pavla; Řezáčová, Pavlína; Brynda, Jiří; Lepšík, Martin; Mertlíková-Kaiserová, Helena; Emal, Cory D; Renslo, Adam R; Roush, William R; Horn, Martin; et al. (ACS infectious diseases, 2021)
Schistosomiasis, a parasitic disease caused by blood flukes of the genus Schistosoma, is a global health problem with over 200 million people infected. Treatment relies on just one drug, and new chemotherapies are needed. Schistosoma mansoni cathepsin B1 (SmCB1) is a critical peptidase for the digestion of host blood proteins and a validated drug target. We screened a library of peptidomimetic vinyl sulfones against SmCB1 and identified the most potent SmCB1 inhibitors reported to date that are active in the subnanomolar range with second order rate constants (k2nd) of ∼2 × 105 M-1 s-1. High resolution crystal structures of the two best inhibitors in complex with SmCB1 were determined. Quantum chemical calculations of their respective binding modes identified critical hot spot interactions in the S1' and S2 subsites. The most potent inhibitor targets the S1' subsite with an N-hydroxysulfonic amide moiety and displays favorable functional properties, including bioactivity against the pathogen, selectivity for SmCB1 over human cathepsin B, and reasonable metabolic stability. Our results provide structural insights for the rational design of next-generation SmCB1 inhibitors as potential drugs to treat schistosomiasis.
Keywords: cathepsin B; Schistosomiasis; parasite; sulfony; Sulfones; Cathepsin B; schistosomóza; cysteine peptidase; Animals; lidé; kathepsin B; drug target; Schistosoma mansoni; vinyl sulfone inhibitor; zvířata; Humans